Answer:
![f(x)=4x](https://img.qammunity.org/2023/formulas/mathematics/high-school/3o7r8mqqww1exdrfgzcpnh86dvxeerfb0m.png)
Step-by-step explanation: According to the power rule of taking a derivative, if we have a certain function:
![f(x)=Cx^n+K](https://img.qammunity.org/2023/formulas/mathematics/college/p7fj9vk3xgcvhuujz0yubn0w8j8mpv95b8.png)
Then the derivative of the f(x) would be as follows:
![\begin{gathered} (df(x))/(dx)=(d(Cx^n))/(dx)+(d(K))/(dx)=(d(Cx^n))/(dx)+0 \\ \text{ Implies }\Rightarrow(d(K))/(dx)=0 \\ \therefore\Rightarrow \\ (df(x))/(dx)=(d(Cx^n))/(dx)=C\cdot nx^((n-1)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3vhndf4q01qokkho2wiuapucobvebqwmvr.png)
Using this rule in reverse we can calculate the antiderivative of the provided f(x) as follows:
![\begin{gathered} (dF(x))/(dx)=(d(Cx^n))/(dx)+(d(K))/(dx)=f(x)=4 \\ K=0 \\ \therefore\Rightarrow \\ (dF(x))/(dx)=(d(Cx^n))/(dx)=4\Rightarrow4x\Rightarrow C=4 \\ \text{ }\therefore\rightarrow \\ f(x)=4x \\ \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/aro8fkp47n1zvewe1055qabphbzorfo70j.png)